THE RELATION PREECLAMPSIA WITH HEMORRHAGIC POST PARTUM (HPP) AT AURA SYIFA HOSPITAL KEDIRI 2015 YEARS - Siti Asiyah Siti Asiyah Siti Asiyah (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2015)
Pregnancy have a tall risk anomaly and directly can causes painfulness and also baby. One of the pregnancy risk that factor can causes mother death is preeclampsia and delivery complications that cause death are Haemoragic Post partum. This plan research detects relation between preeclampsia with hemorrhagic post partum, at Aura Syifa Hospital Regency Kediri 2015 years. Research design crosectional with approach kohort retrospective. Variable independent preeclampsia and variable dependent hemorrhagic post partum with population 74 respondents and sample 62 respondents with technique sampling Simple random sampling with analysis chi quadrate. Data was gathered in this secondary data. Data secondary that was gathered from other party that data collectors sheet adopted from rekam medical in a birth. This research was done at Aura Syifa Hospital Kediri on June 2015. Based on relation analysis uses Chi Quadrat get result p value=0,000 < a=0,05, while the correlation coefficient result 0,695 that mean Ho adversed with positive relation with strong relation so that meaning from the result there relation pregnancy preeclampsia with incident hemorrhagic post partum at Aura Syifa Hospital Kediri 2015 years. Preeclampsia will evoke hipofibrenemia thereby will have in trombosite that was will experience trombositomia so that will emerge lengthways coagulation so will be experience haemoragic because the coagulation substance will not functioned maximal.